Suggestopedia: Answering English Collaborative Learning Concept in Disruptive Era 4.0 - Vidi Ferdinand Wenas Sampow (Institut Agama Islam Negeri (IAIN) Manado, 2021)
Suggestopedia: Answering English Collaborative Learning Concept in Disruptive Era 4.0 Suggestopedia is a representation of a teaching method that is integrated with students' learning preferences and is used as a collaborative learning method to achieve quality education that is in line with the rapid development of technology and it is answering the English collaborative learning concept in disruptive era 4.0. This study aims to investigate the effectiveness of suggestopedia in the teaching of English. This study is also supported by the results of students’ statement about suggestopedia for their English learning and its contribution to collaborative learning concept in industrial revolution 4.0. The method used was pre-experimental design of one group pre-test and post-test. The instruments were a multiple choice English test and questionnaire to gain the students’ perspective on the implementation of suggestopedia. The results revealed that the students performed better in the post-test of English skill than in the pre-test.Keywords: Suggestopedia, collaborative learning, method, digitalization.